Factors affecting the acceptance of e-wallet system among young adults: a case study in Ipoh, Perak / Muhammad Firdaus Aminuddin - Aminuddin, Muhammad Firdaus (2018)
E-wallet or Mobile wallet can be defined as a secure place that used mobile technology as a way to carry your credit card or debit card information in a digital form on your mobile device. Instead of using your physical plastic card to make purchases, you can pay with your smartphone, tablet, or smartwatch. As for now, the e-wallet apps that are available in Malaysia are Alipay, Razer Pay, Samsung Pay, Mol-Pay, Boost and Grab-Pay. The technological advancement combined with the growing use of smartphones has increased its capabilities such as functions like able to perform a purchase and payment transactions. This technological marvel had impacted worldwide and provides individuals more flexibility and convenience in carrying out their daily activities. All in all, this study aims to investigate the factors affecting the acceptance of E-Wallet System among young adults in Ipoh, Perak. The objective is to find out whether performance expectation, effort expectation, social influence, perceived cost and perceived risk would influence behavioral intention to adopt e-wallet. Self-administered questionnaire is used the data collection tool with 200 samples from Ipoh, Perak are collected for data analysis. The significant variable that could influence the behavioral intention to adopt e-wallet has been discovered which is performance expectation, effort expectation and social influence. The implication and limitation of this study were discussed at the end of this paper.